Optimization of Adjuvant Radiation in Breast Conservation Therapy: Can We Minimize without Compromise? - Sophia M. Edwards-Bennett; Candace R. Correa; Eleanor E. Harris (International Journal of Breast Cancer)
Adjuvant breast radiation therapy after breast conservation surgery is recommended as it yields significant reduction in the risk of local recurrence, and confers a potential overall survival benefit. Although the standard breast radiation regimen has historically been delivered over 5–7 weeks; more novel, shorter courses of breast radiation are currently being employed, offering the advantage of more convenience and less time-commitment. Herein, we review the recent literature substantiating these abbreviated radiation treatment approaches and the methods of delivery thereof. In addition, we discuss imaged guided techniques currently being utilized to further refine the delivery of adjuvant breast radiation therapy.